The current status of preclinical proton FLASH radiation and future directions. Issue 3 (26th October 2021) - Diffenderfer, Eric S.; Sørensen, Brita S.; Mazal, Alejandro; Carlson, David J.
Abstract: We review the current status of proton FLASH experimental systems, including preclinical physical and biological results. Technological limitations on preclinical investigation of FLASH biological mechanisms and determination of clinically relevant parameters are discussed. A review of the biological data reveals no reproduced proton FLASH effect in vitro and a significant in vivo FLASH sparing effect of normal tissue toxicity observed with multiple proton FLASH irradiation systems. Importantly, multiple studies suggest little or no difference in tumor growth delay for proton FLASH when compared to conventional dose rate proton radiation. A discussion follows on future areas of development with a focus on the determination of the optimal parameters for maximizing the therapeutic ratio between tumor and normal tissue response and ultimately clinical translation of proton FLASH radiation.